Complement 3a Mediates CCN2/CTGF in Human Retinal Pigment Epithelial Cells. (30th July 2022) - Xiao, Kang; Xu, Zhiyan; Chen, Zhengyu; Long, Qin; Chen, Youxin
Abstract : Background . Complement 3 (C3) is the crucial component of the complement cascade when retina was exposed to external stimulus. Cellular communication network 2/connective tissue growth factor (CCN2/CTGF) is important in response of retinal stress and a fulcrum for angiogenesis and fibrosis scar formation. Our study aims to explore the interaction between C3 and CCN2/CTGF via bioinformatics analyses and in vitro cell experiments. Methods . The GSE dataset was selected to analyse the chemokine expression in human retinal pigment epithelium (ARPE-19) cells under stimulus. Then, RPE cells were further transfected with or without C3 siRNA, followed by C3a (0.1 μ M or 0.3 μ M) for 24, 48, and 72 hours. Reverse transcription-polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA) were used to measure CCN2/CTGF mRNA and protein levels. Results . The GSE36331 revealed C3 expression was significantly elevated in RPE under stimulus. Compared with negative control, CCN2/CTGF mRNA was increased with all types of C3a treatments, whereas a significant increase of protein level was only observed with high concentration of 0.3 μ M C3a for a prolonged 72-hour time. Compared with nontransfected cells, significant reductions of CCN2/CTGF mRNA were observed in the C3 siRNA transfected cells with 0.3 μ M C3a for 24, 48, and 72 hours, and a significant reduction of CCN2/CTGF protein was observed with 0.3 μ M C3a for 48 hours. Conclusions . C3 was elevated in RPE under environmental stimulus and long-term exposure to specified concentration of C3a increased CCN2/CTGF expression in RPE, which could be partially reversed by C3 siRNA.